COMBINATION OF GEOPHYSICAL TECHNIQUES FOR MAPPING AND MONITORING OF RADIOACTIVE WASTE DISPOSAL FACILITIES - Popov, S.; Bondar, К.; Khomenko, R.; Bondarkov, М.; Maksymenko, А. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Sites of radioactive waste disposal in Chernobyl exclusion zone still contain significant amounts of fissile materials. At the same time, the information on the amount of radioactive material buried during the accident cannot be called satisfactory. Within the strengthening international safety and environmental requirements, special activities were initiated to survey the radioactive waste disposals created during the liquidation of the accident at the Chernobyl nuclear power plant. The work involved the following combination of non-invasive geophysical methods: 1) high-resolution magnetometry; 2) ground penetrating radar (GPR) 3) direct current electrical resistivity tomography (ERT). Magnetometry provided the detailed map of facilities, and highlighted the sites where containers with fissile substances had been buried. ERT models revealed variations in the resistivity across the disposal site, which is associated with different water content, and may indicate flooding. Ground water level was determined from GPR mesurements. The combined interpretation of geophysical results served a basis for designing the geometric model of the "Chernobyl 3rd stage" radioactive waste disposal facility. It was used to determine the places for subsequent applying direct radioactive methods for investigation and monitoring of this disposal site. Keywords: magnetometry, electrical resistivity tomography, ground penetrating radar, radiation dose, radioactive waste, groundwater.
Keywords: magnetometry; electrical resistivity tomography; ground penetrating radar; radiation dose; radioactive waste; groundwater